(untitled) (Zia e Tahqeeq, 2025)
Islam has taught to maintain good relations with non-Muslims and pay their payments irrespective of differences of faith. The real thing in relations with non-Muslims is peace, not war. The Qur’an says that no one can force anyone to accept Islam. One issue is whether non- Muslims will have the right to a key position or jobs in a Muslim state. Those who consider Islam to be a religion revealed by God Almighty can only run a Muslim state sincerely. On the contrary, those who do not believe in Islamic teaching and don’t consider it a religion revealed by God will not correctly run a Muslim state. Therefore, they are not suitable for its key positions. This paper argues that apart from the key positions, there is equal opportunities must be granted to the non-Muslims for employment and it is responsibility of a Muslim State to create freedom to work for non-Muslims